Lesbian, gay and bisexual teachers' ambivalent relations with parents and students while entering into a civil partnership. Issue 1 (2nd January 2017) - Neary, Aoife
Abstract : Schools are quasi-public/private organisations and being a teacher involves negotiating personal and professional boundaries. These boundaries have posed particular challenges for lesbian, gay, bisexual, transgender and queer (LGBT-Q) teachers whose everyday lives are complicated by legislative, religious and cultural constraints, moral panics about childhood innocence, reductive discourses about sexuality and negative stereotypes. In many contexts, the past decade has seen rapid change in the politics of sexuality as legal structures for same-sex relationships have emerged and promised normalisation for LGBT-Q people. Such developments raise questions about how these changing politics of sexuality are spilling over into school contexts. In Ireland, entering into a civil partnership (CP) altered the shape of LGB teachers' relations with their colleagues in schools. But neoliberal systems of performance and accountability coalesce with a persisting uncomfortable relationship between LGBT-Q identification and schooling ensuring that LGBT-Q teachers have different kinds of relations with parents and students. This paper provides new insight into these relations as LGB teachers entered into a CP. I argue that their work to manage these relations had ambivalent effects. Fore-fronting a high-performing professional subjectivity and maintaining distances with students while acting as agents of change (re)produced heteronormativity but simultaneously enabled moments that promised queer, transgressive potential.